Assessment of home care aides' respiratory exposure to total volatile organic compounds and chlorine during simulated bathroom cleaning: An experimental design with conventional and "green" products - Lindberg, J. E.; Quinn, M. M.; Gore, R. J.; Galligan, C. J.; Sama, S. R.; Sheikh, N. N.; Markkanen, P. K.; Parker-Vega, A.; Karlsson, N. D.; LeBouf, R. F.; Virji, M. A. (Journal of occupational and environmental hygiene, 2021)
Home care (HC) aide visits to clients' homes often involve cleaning and disinfecting (C&D) bathrooms. Some ingredients in C&D household products are associated with respiratory illness, including sodium hypochlorite (bleach) and quaternary ammonium compounds (quats). "Green" products may be safer for the environment, however there are limited quantitative evaluations of their respiratory risks. This study assessed airborne concentrations and time profiles of total volatile organic compounds (TVOC) and chlorine generated during typical bathroom cleaning performed by aides using conventional and green products. Aides performed cleaning tasks in a simulated residential bathroom constructed in an environmental air sampling laboratory. A balanced experimental design involved each aide coming to the lab for four visits during which she performed two 20-min cleaning sessions using one of three C&D products (bleach-based, 1-5% sodium hypochlorite by weight; quats-based, 0.1-1% by weight quaternary ammonium compounds; and "green," 0.05% by weight thymol, a component of botanical thyme oil) or distilled water as a control. TVOC and chlorine direct reading instruments were attached to aides with sample inlets located in the breathing zone. Ten-second averages of TVOC and chlorine gas concentrations and instantaneous peak concentrations were recorded for the sessions' duration. TVOC concentrations by methods of C&D application (spraying, streaming, wiping) also were evaluated. The study completed 169 air sampling sessions with 22 aides. The quats-based product generated more than twice the average TVOC concentrations (mean = 1,210 ppb) than the bleach-based (mean = 593 ppb) or green (mean = 498 ppb) products. Each product generated TVOC concentrations that rose rapidly within the first few minutes of application. Spraying produced the highest TVOC exposures, wiping the lowest. Thirteen aides (65%) experienced peak chlorine exposures above the OSHA PEL ceiling limit (1 ppm) when using the bleach-based product. HC aides may experience respiratory hazards from use of conventional or green C&D products formulated with bleach or other respiratory irritants and sprayed in small, poorly ventilated spaces typical of bathrooms. Spraying should be avoided.